Predicting the Performance of Certain Fundamental Skills Based on Selected Physical Tests for Young Football Players in Mosul Academies - Younis, Anmar Abdul-Munem; Al-Dhahir, Shihab Ahmed; Jumaa, Jumaa Ismail (Universitas Majalengka, 2025)
The measurement process in physical education and sports sciences, which focus on motor behavior, is more complex than in other sciences due to internal and external factors' significant and immediate influence on humans. Consequently, there is growing interest in tests essential to life, work, and performance. This study aims to establish predictive equations for skill tests based on several physical tests for young football players in the Mosul city academies. The researchers used a descriptive correlational method as it suits the nature of the research problem. The research sample consisted of young players, totaling (96), after excluding the pilot experiment sample, the reliability, and the players absent from the tests, which amounted to 74 players. Thus, the research sample represented (56.47%) of the total population of the study. The results of this work show that the physical tests used in the research contributed significantly to the results of the dribbling and passing skill tests, which underscores the importance of the physical tests in assessing the dribbling and passing skills of young football players in the academies of Mosul City. In conclusion, the research concluded that physical tests are effective for young players in the Mosul City academies.